2020
DOI: 10.3389/fbioe.2020.00581
|View full text |Cite
|
Sign up to set email alerts
|

Bringing Safe and Standardized Cell Therapies to Industrialized Processing for Burns and Wounds

Abstract: organ donation potentially enables millions of patients to benefit from high-quality, safe and effective regenerative therapies. This work presents a technical and translational overview of the described progenitor cell technology harnessed in Switzerland as cellular therapies for treatment of burns and wounds around the globe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
71
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 14 publications
(109 citation statements)
references
References 63 publications
1
71
0
Order By: Relevance
“…Regulatory vetting and GMP constraints relative to traceable tissue procurement, testing, and bioprocessing favor an up-stream medical and serological testing approach (i.e., repeated bloodwork for HIV-1/2, HTLV-1/2, hCMV, EBV, HHV-6/7/8, HSV, HBV, HCV, HPV, West Nile virus, syphilis) of motherdonors for inclusion in the Program, positively impacting longterm testing costs ( Supplementary Figure 1; Quintin et al, 2007;Applegate et al, 2013). Practically, optimized workflows and specifications eventually enabled traceable simultaneous isolation of various FPC types (i.e., FPCs isolated from fetal tissues such as skin, cartilage, tendon, bone, muscle, intervertebral disc, lung) from a single fetal organ donation (i.e., codename FE002, 2009) for rapid and efficient PCB establishment and subsequent industrial GMP processing (Laurent et al, 2020e). Specific bioprocessing methodologies enable safe and sustained use of original cell sources for extended periods, as adequate testing implementation ensures maximal safety of the end-products or substrates (De Buys Roessingh et al, 2015).…”
Section: Swiss Fetal Transplantation Programsmentioning
confidence: 99%
See 4 more Smart Citations
“…Regulatory vetting and GMP constraints relative to traceable tissue procurement, testing, and bioprocessing favor an up-stream medical and serological testing approach (i.e., repeated bloodwork for HIV-1/2, HTLV-1/2, hCMV, EBV, HHV-6/7/8, HSV, HBV, HCV, HPV, West Nile virus, syphilis) of motherdonors for inclusion in the Program, positively impacting longterm testing costs ( Supplementary Figure 1; Quintin et al, 2007;Applegate et al, 2013). Practically, optimized workflows and specifications eventually enabled traceable simultaneous isolation of various FPC types (i.e., FPCs isolated from fetal tissues such as skin, cartilage, tendon, bone, muscle, intervertebral disc, lung) from a single fetal organ donation (i.e., codename FE002, 2009) for rapid and efficient PCB establishment and subsequent industrial GMP processing (Laurent et al, 2020e). Specific bioprocessing methodologies enable safe and sustained use of original cell sources for extended periods, as adequate testing implementation ensures maximal safety of the end-products or substrates (De Buys Roessingh et al, 2015).…”
Section: Swiss Fetal Transplantation Programsmentioning
confidence: 99%
“…Bioengineered PBB constructs were observed to promote proliferation, adhesion, and migration of endogenous cells, without atrophic skin formation (Ramelet et al, 2009). Over two decades of clinical experience and multicentric studies have shown the safety or beneficial therapeutic effects of dermal FPCs in PBBs, notably within phase I and II clinical trials in Switzerland and Asia (i.e., ClinicalTrials.gov identifiers: NCT02737748 & NCT03624023) (Hohlfeld et al, 2005;Ramelet et al, 2009;Laurent et al, 2020e). In view of further optimization of burn wound or ulcer care in particular, high therapeutic benefits may be gained by stabilizing and formulating active cell-derivative components in pharmaceutical creams, ointments, or gels, as these are used for the maintenance therapy to accelerate wound healing (i.e., potentially scarlessly) after primary wound closure.…”
Section: Swiss Tools For Cutaneous Regeneration: Progenitor Biologicamentioning
confidence: 99%
See 3 more Smart Citations